Chemistry Techniques and Explorations An Introductory Chemistry Laboratory Manual - Albert, Daniel R. (Open textbook library., 2023)
Chemistry Techniques and Explorations (2023) by Dr. Daniel R. Albert is an eTextbook laboratory manual for first semester introductory chemistry courses. The manual includes two different types of experiments (Technique and Exploration) designed to engage students in chemistry laboratory practices. Technique laboratories are designed for students to learn and practice chemistry laboratory skills that are utilized in a wide variety of disciplines. Exploration laboratories provide freedom and time for students to use previously acquired skills toward answering a new application focused question. Exploration laboratories help build the scientific thinking skills necessary to approach novel problems. The goal of this lab manual is to build both fundamental techniques and problem-solving skills that aid students in becoming practicing scientists.